2015
DOI: 10.1534/genetics.115.174698
|View full text |Cite
|
Sign up to set email alerts
|

Class I Myosins Have Overlapping and Specialized Functions in Left-Right Asymmetric Development inDrosophila

Abstract: The class I myosin genes are conserved in diverse organisms, and their gene products are involved in actin dynamics, endocytosis, and signal transduction. Drosophila melanogaster has three class I myosin genes, Myosin 31DF (Myo31DF), Myosin 61F (Myo61F), and Myosin 95E (Myo95E). Myo31DF, Myo61F, and Myo95E belong to the Myosin ID, Myosin IC, and Myosin IB families, respectively. Previous loss-of-function analyses of Myo31DF and Myo61F revealed important roles in left-right (LR) asymmetric development and enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 82 publications
(186 reference statements)
1
47
0
Order By: Relevance
“…Overexpression of both Drosophila proteins in Xenopus results in the observation of heterotaxia in various organs. Most striking is that only recently were the tissue-specific functions of these proteins identified in Drosophila , and it appears that Myo61F is important in genitalia-turning, whereas Myo31DF is involved in the stomach (47). Myosin1d, the homologue of Myo31DF, affects stomach laterality in all observed cases of heterotaxia (Supplementary Figure 1), but the frog homologues of Myo61F apparently have no effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of both Drosophila proteins in Xenopus results in the observation of heterotaxia in various organs. Most striking is that only recently were the tissue-specific functions of these proteins identified in Drosophila , and it appears that Myo61F is important in genitalia-turning, whereas Myo31DF is involved in the stomach (47). Myosin1d, the homologue of Myo31DF, affects stomach laterality in all observed cases of heterotaxia (Supplementary Figure 1), but the frog homologues of Myo61F apparently have no effect.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with a very broad conservation, the same targets were implicated in generating a consistent laterality across the tree of life. Notably, effects on organ positioning of the gut observed in Drosophila with Myo31DF overexpression (47) are replicated in Xenopus with the frog homologue Myo1D; and the dissociation of left-right organ positioning from Nodal expression observed in mouse mahogunin (Mgrn1) mutants (48) is replicated in Xenopus. We show that some of these steps occur very soon after fertilization and not at later stages (when cilia could be functioning).…”
Section: Introductionmentioning
confidence: 99%
“…Myo31DF is a member of the unconventional myosin I class; these molecules consist of an N-terminal head domain containing an ATP-binding motif, a neck domain containing two calmodulin-binding IQ motifs, and a short C-terminal tail domain [27,29,30]. A mutant Myo31DF protein lacking the IQ motifs is unable to rescue the Myo31DF phenotype [29].…”
Section: Myosin31df Switches the Cell Chirality In Drosophilamentioning
confidence: 99%
“…[210]. Very recently, the Matsuno laboratory has demonstrated that besides MyoID other myosin I motors have overlapping functions with MyoID in tissue chirality [211]. Thus, D. melanogaster type I myosins seem to generate chiral forces by interacting with actin filaments.…”
Section: Melanogastermentioning
confidence: 99%